Community Support in The Implementation of School-Based Management - Apri Retnaningsih; Achadi Budi Santosa (RIRAI Publisher, 2020)
This study aims to reveal the role and participation of the community in the implementation of School-Based Management (SBM) and the factors supporting and inhibiting implementation. The research was conducted using observation sheet guides and interview guidelines supported by a review of school administration documents, through a qualitative approach to the interactive analysis model of Miles and Huberman. The results showed that the implementation of SBM was quite successful; this was indicated by a significant change in schools, namely the increase in school quality and increased public interest in Muhammadiyah Mutihan Elementary School. In the implementation of SBM, the school is more flexible because it can manage schools independently, making programs based on the school's needs and abilities. Public participation is quite good; the community always supports and helps school activities and controls the school. Supporting factors in implementing SBM are the community, alumni, foundations, and sponsors. While the inhibiting factor is limited land, schools cannot provide sports fields for students and the limited ability to accompany teachers.